Microenvironments of tuberculous granuloma: advances and opportunities for therapy - Krueger, Gesa; Faisal, Shah; Dorhoi, Anca (Frontiers in Immunology, 2025)
The hallmark tissue lesions of tuberculosis (TB) are granulomas. These multicellular structures exhibit varying degrees of cellular complexity, are dynamic, and show considerable diversity within and between hosts. Categorization based on gross pathologic features, particularly caseation and necrosis, was historically coined prior to the identification of mycobacteria as the causative agent of TB. More recently, granuloma zonation based on immune cell composition, metabolite abundance, and physical characteristics has gained attention. With the advent of single-cell analyses, distinct microenvironments and cellular ecosystems within TB granulomas have been identified. We summarize the architecture of TB granulomas and highlight their cellular heterogeneity, including cell niches as well as physical factors such as oxygen gradients that modulate lesion fate. We discuss opportunities for therapy, highlighting new models and the power of in silico modeling to unravel granuloma features and trajectories. Understanding the relevance of the granuloma microenvironment to disease pathophysiology will facilitate the development of more effective interventions, such as host-directed therapies for TB.